Representasi Tsunami Tendenko dalam Ehon Hana Chan no Haya Aruki Haya Aruki karya Ube Kyouko - Revisya Dwi Venesca Putri; Silvia Damayanti; I Made Budiana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This study investigates the representation of the disaster mitigation concept known as “Tsunami Tendenko,” a form of local wisdom originating from the Sanriku region of Japan. The concept has gained prominence due to its principle that contrasts with the conventional moral teachings of disaster response across Japan, which emphasize mutual aid. In contrast, “Tsunami Tendenko” prioritizes individual self-preservation. This study employs a descriptive-analytical method, using observation and note-taking as data collection techniques. The analysis identifies four core principles of “Tsunami Tendenko” as represented in the picture book Hana Chan no Haya Aruki Haya Aruki by Ube Kyouko: (1) taking personal responsibility for one’s own safety, (2) encouraging others to evacuate, (3) fostering mutual trust, and (4) reducing self-blame among disaster survivors. The study also reveals the pedagogical impact represented in the picture book, namely reducing disaster casualties, fostering disaster awareness and responsiveness, and promoting acceptance of disaster victims. This concept continues to develop as relevant local wisdom in the context of modern-day evacuation and disaster mitigation